2005
DOI: 10.1007/s00280-005-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Chloroacetaldehyde: mode of antitumor action of the ifosfamide metabolite

Abstract: In summary, our results show that chloroacetaldehyde influences the oxidative phosphorylation in mitochondria, however, this is observed only in high concentrations and is not of clinical relevance because the tumor cells regenerate ATP by anaerobic glycolysis. Nevertheless, chloroacetaldehyde causes DNA-strand-breaks and strong inhibition of DNA-synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…6A). This mode of action may explain previous observations indicating that CAA depleted cellular reduced glutathione and ATP, disturbed Ca 2+ signaling, lipid peroxidation, and, ultimately, cell necrosis and death (8,(35)(36)(37)(38)(39). The cytotoxic effect of CAA is likely due to low or no reactivity with MESNA (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…6A). This mode of action may explain previous observations indicating that CAA depleted cellular reduced glutathione and ATP, disturbed Ca 2+ signaling, lipid peroxidation, and, ultimately, cell necrosis and death (8,(35)(36)(37)(38)(39). The cytotoxic effect of CAA is likely due to low or no reactivity with MESNA (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…In addition to the curtailment of ATP synthesis, dysfunction of C-I may lead to elevated production of superoxide radicals, causing mitochondrial DNA mutations, lipid peroxidation, and protein denaturation (35)(36)(37)(38). The current study shows that the IFOinduced inhibition of NADH:oxidoreductase was associated with a significant elevation of [NADH], inhibition of the flux through the PDH reaction, and incorporation of acetyl-CoA (derived from pyruvate) into the TCA cycle (Figs.…”
Section: Discussionmentioning
confidence: 69%
“…Although the semimustard products of dealkylation are not themselves able to cross-link DNA and thus have low cytotoxic potency , the other dealkylation products are reactive aldehydes. Thus, dealkylation of oxazaphosphorine mustards forms chloroacetaldehyde, which has been reported to cross-link DNA (Spengler and Singer, 1988), induce DNA breaks, and inhibit DNA synthesis (Brüggemann et al, 2006). Chloroacetaldehyde is a potent cytotoxin in vitro (Brüggemann et al, 1997), shows antitumor activity in vivo (Börner et al, 2000), is neurotoxic (Goren et al, 1986;Lewis and Meanwell, 1990), is nephrotoxic (Skinner et al, 1993), and is considered to contribute to the clinical toxicity of oxazaphosphorine mustards (Zhang et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…An equimolar amount of chloroacetaldehyde (CAA, 10) is formed in each of these N-dealkylation reactions. This metabolite is known to be responsible for both nephrotoxicity and neurotoxicity, which may be associated with IFO treatment (Boddy and Yule, 2000;Chatton et al, 2001;Ajithkumar et al, 2007), even if it has been recently reported that CAA could contribute to IFO cytotoxicity (Brü ggemann et al, 2006). Reducing CAA formation may reduce frequency of IFO-related neurotoxicity and nephrotoxicity.…”
mentioning
confidence: 99%